FDG-PET/CT in the Radiotherapy Treatment Planning of Locally Advanced Anal Cancer: A Monoinstitutional Experience - Di Carlo, Clelia; di Benedetto, Maika; Vicenzi, Lisa; Costantini, Sara; Cucciarelli, Francesca; Fenu, Francesco; Arena, Eleonora; Mariucci, Cristina; Montisci, Maria; Panni, Valeria; Patani, Fabiola; Valenti, Marco; et al. (Frontiers in Oncology, 2021)
Aims Radiotherapy with concurrent 5-fluorouracil/mitomycin-C based chemotherapy has been established as definitive standard therapy approach for anal cancer. Intensity Modulated Radiotherapy (IMRT) leads to a precise treatment of the tumor, allowing dose escalation on Gross Tumor Volume (GTV), with a surrounding healthy tissues sparing. Our study assessed the impact of 18-Fluorodeoxyglucose positron emission tomography (18FDG-PET/CT) on the radiotherapy contouring process and its contribution to lymphatic spread detection, resulting a personalization of Clinical Target Volume (CTV) and dose prescription. Methods Thirty-seven patients, with histologically proven squamous cell carcinoma of the anal canal (SCCAC) were analyzed. All patients were evaluated with history and physical examination, trans-anal endoscopic ultrasound, pelvis magnetic resonance imaging (MRI), computed tomography (CT) scans of the chest, abdomen and pelvis and planning 18FDG-PET/CT. The GTV and CTV were drawn on CT, MRI and 18FDG-PET/CT fused images. Results Thirty-four (91%) out of 37 patients presented lymph nodes involvement, in one or more areas, detected on 18FDG-PET/CT and /or MRI. The 18FDG-PET/CT showed positive lymph nodes not detected on MRI imaging (PET +, MRI-) in 14/37 patients (38%). In 14 cases, 18FDG-PET/CT allowed to a dose escalation in the involved nodes. The 18FDG-PET/CT fused images led to change the stage in 5/37(14%) cases: 4 cases from N0 to N1 (inguinal lymph nodes) and in 1 case from M0 to M1 (common iliac lymph nodes). Conclusions The 18FDG-PET/CT has a potentially relevant impact in staging and target volume delineation/definition in patients affected by anal cancer. In our experience, clinical stage variation occurred in 14% of cases. More investigations are needed to define the role of 18FDG-PET/CT in the target volume delineation of anal cancer.